INTEGRATION MANAGEMENT OF ALTERNARIA BLIGHT OF PIGEONPEA WITH SOME FUNGICIDES AND ANTAGONISTS IN POT CONDITION - BALAI, LAXMAN PRASAD; R. B. SINGH (The Bioscan, 2012)
The pot culture studies were found out to be the effect of seed treatment, foliar spray and seed treatment + foliar with six fungicides, two antagonist and their combinations on alternaria blight of pigeonpea. Artificial inoculation of mass culture of Alternaria tenuissima was done in the inoculated seed treatment and after foliar spray on the plants sixty DAS to create the desirable level of disease pressure of the pathogen. Among them twenty five seed treatments, combination of Mancozeb with Trichoderma viride was found to be most effective in reducing the disease intensity and disease control (6.15 and 71.08%) followed by Mancozeb with T. harzianum (6.28 and 70.45%) and Mancozeb (6.35 and 70.14%) alone, respectively. In case of foliar spray of Mancozeb with T. viride was found most effective in reducing the disease intensity and disease control (11.92 and 71.29%) followed by combination of Mancozeb with T. harzianum (12.11 and 70.82%) and Mancozeb alone (12.25 and 70.48%) treatment, respectively. In case of both seed treatment and foliar spray of Mancozeb with T. viride was found most effective in reducing the disease intensity and disease control (11.37 and 72.69%) followed by combination of Mancozeb with T. harzianum (11.43 and 72.53%) and Mancozeb (11.49 and 72.40%) alone, respectively. Whereas least effective and maximum disease intensity and disease control were observed T. harzianum (33.85 and 18.67%) alone as compared to control.